2006
DOI: 10.1111/j.1741-3729.2006.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

The O*Net Jobs Classification System: A Primer for Family Researchers

Abstract: Abstract:We introduce family researchers to the Occupational Information Network, or O*Net, an electronic database on the work characteristics of over 950 occupations. The paper here is a practical primer that covers data collection, selecting occupational characteristics, coding occupations, scale creation, and construct validity, with empirical illustrations from the Family Life Project, a study of almost 1,300 families with infants born in 6 lowincome, nonmetro counties in North Carolina and Pennsylvania. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…In addition, one of those two earlier studies carried out a second-order EFA and found the same three-factor structure as we did among the first-order O*NET subdomain factor scores. 25 Furthermore, a number of previous PCA/EFA studies of individual O*NET subdomains 25 and more limited sets of O*NET dimensions 20,24,3335 found within-subdomain components/factors were similar to most of those identified here.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, one of those two earlier studies carried out a second-order EFA and found the same three-factor structure as we did among the first-order O*NET subdomain factor scores. 25 Furthermore, a number of previous PCA/EFA studies of individual O*NET subdomains 25 and more limited sets of O*NET dimensions 20,24,3335 found within-subdomain components/factors were similar to most of those identified here.…”
Section: Discussionsupporting
confidence: 80%
“…Inspired by Zimmerman et al,(2004), Crouter et al (2006), Meyer et al (2007), Alterman et al (2008) and Bell et al (2008), exploratory factor analysis was used to combine variables from the O*Net database. Overall Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was 0.94 indicating the occupational attribute variables had sufficient commonality to warrant a factor analysis (Kaiser, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Using data from the Occupational Information Network (O * Net; Peterson et al, 2001), which has been validated previously (Crouter, Lanza, Pirretti, Goodman, & Neebe, 2006), objective measures of maternal and paternal occupational characteristics were constructed using parents’ job descriptions. The O * Net electronic database contains data reflecting the character of occupations that allows for the comparison of attributes (e.g., knowledge, skills, activities, tasks) within and across occupations.…”
Section: Methodsmentioning
confidence: 99%